Safe, Effective Chin and Jaw Restoration With VYC-25L Hyaluronic Acid Injectable Gel. Issue 10 (October 2019) - Ogilvie, Patricia; Sattler, Gerhard; Gaymans, Frodo; Belhaouari, Lakhdar; Weichman, Barry M.; Snow, Sean; Chawla, Smita; Abrams, Steve; Schumacher, Andrew
Abstract : BACKGROUND: VYC-25L, a hyaluronic acid soft-tissue filler with lidocaine, is designed to restore and create facial volume in the chin and jaw. OBJECTIVE: To evaluate the safety and effectiveness of VYC-25L in subjects with chin retrusion. METHODS: Adults with chin retrusion (145°–165° glabella–subnasale–pogonion facial angle) were randomized (3:1) to receive VYC-25L in the chin/jaw at study onset (treatment group) or 3 months later (control group). Primary effectiveness end point was mean change in facial angle from baseline at Month 3. Safety assessments included injection site responses (ISRs), recorded in a subject diary, and adverse events (AEs). RESULTS: VYC-25L was administered to 119 subjects (treatment group: n = 90; control group: n = 29). Mean change in facial angle from baseline at Month 3 was significantly greater in the treatment versus control group (difference: 2.51°; p < .0001). Effectiveness was also demonstrated by the proportion of subjects with improved/much improved Global Aesthetic Improvement Scale scores and responses on FACE-Q Satisfaction and Psychological Well-Being Scales. Treatment benefit remained evident at Month 12. Common ISRs were firmness (95.8%), tenderness (95.8%), and swelling (91.6%). No serious treatment-related AEs were reported. CONCLUSION: VYC-25L significantly improved glabella–subnasale–pogonion facial angle and was generally safe and well tolerated. Abstract : Supplemental Digital Content is Available in the Text.